2013
DOI: 10.1002/pat.3124
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy‐cyanate ester shape memory thermoset: some aspects of phase transition, viscoelasticity and shape memory characteristics

Abstract: A shape memory thermoset comprising of a co‐reacted system of epoxy resin (diglycidylether of bisphenol A), cyanate ester (bisphenol A dicyanate ester) and phenol telechelic poly(tetramethylene oxide) (PTOH) was investigated for its morphology, viscoelasticity and shape memory characteristics at the transition temperature regime. The system exhibited a switching temperature (Tswitch) centered at about 105°C. Atomic force microscopy analyses at different temperatures provided evidences for the existence of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Various manipulations of cyanate-based SMPs have been investigated, and most of these studies have used polybutadiene (Wang et al, 2014a; Xie et al, 2014; Zhao et al, 2014), PEG (Xie et al, 2014), and epoxy (Biju et al, 2012a; Biju and Reghunadhan Nair, 2014; Rajendran et al, 2013; Santhosh Kumar et al, 2014; Wang et al, 2014a) as mobile flexible segments. Xie et al (2014) prepared a series of cyanate-based high-temperature SMPs using functional PEG or polybutadiene/acrylonitrile (PBAN).…”
Section: Typical Thermoset Smpsmentioning
confidence: 99%
“…Various manipulations of cyanate-based SMPs have been investigated, and most of these studies have used polybutadiene (Wang et al, 2014a; Xie et al, 2014; Zhao et al, 2014), PEG (Xie et al, 2014), and epoxy (Biju et al, 2012a; Biju and Reghunadhan Nair, 2014; Rajendran et al, 2013; Santhosh Kumar et al, 2014; Wang et al, 2014a) as mobile flexible segments. Xie et al (2014) prepared a series of cyanate-based high-temperature SMPs using functional PEG or polybutadiene/acrylonitrile (PBAN).…”
Section: Typical Thermoset Smpsmentioning
confidence: 99%
“…Biju and Nair reported the synthesis of a shape‐memory epoxy network based on a diglycidyl ether of bisphenol A (DGEBA) cured with a pyromellitic dianhydride for possible use in smart actuator systems. Rajendran et al synthesized an epoxy‐cyanate system by coreacting a DGEBA, cyanate ester and phenol telechelic poly(tetramethylene oxide) and studied the correlation between the viscoelastic and shape‐memory properties. Wei at al .…”
Section: Introductionmentioning
confidence: 99%
“…Peak stress was observed at zero time, which suggests the rigidity of the material due to hard-aromatic segments present. Higher the tension, the stiffness of the section decreases and low stress increase the material’s flexibility (Rajendran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the stress value did not decrease to zero; instead, it approached a plateau. The plateau stress is the stored internal energy of the net-points, responsible for the recovery of the original shape during the shape memory effect (Rajendran et al, 2013).…”
Section: Stress Relaxation Studymentioning
confidence: 99%
See 1 more Smart Citation